Occupational switching during the Second Industrial Revolution - Bart Hobijn; Robert S. Kaplan (Federal Reserve Bank of Chicago, 2024)
During the Second Industrial Revolution, in the late nineteenth century, the proliferation of automation technologies coincided with substantial job creation but also a "hollowing out" of middle-skilled job opportunities, which historically offered reliable paths to prosperity. We use recently linked U.S. census data to document three main facts: (i) declining demand for middle-skilled labor in manufacturing corresponded to greater reallocation of workers into comparatively less-skilled occupations; (ii) older workers were more likely to switch to unskilled physical labor; (iii) younger workers led switching into growing occupations affected by automation technologies.
Keywords: J62; N31; N32; O33; 330; automation; occupational choice; technological displacement